The Acceptance and Resharing Behavior of Hoax Information on Social Media - Melisa Arisanty; Gunawan Wiradharma (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2020)
The spread of hoax information on social media is still difficult to control. Various efforts have been made by the government to eradicate hoax information, even the Ministry of Communication and Information has chosen the decision to block accounts that spread hoaxes, especially those on social media. However, hoax information still exists and its spread is increasing. Therefore, it is necessary to have a strategy that is right on target to prevent the spread of hoaxes. To design a strategy that is right on target, it is necessary to identify the acceptance attitude and behavior of sharing hoax information on social media. Through research using an interpretive paradigm and a qualitative research approach with research data collection, namely interviews with 12 (twelve) informants who are part of the community in Banten, West Java and Aceh Provinces. So, an interesting finding was found that currently receiving hoax information that leads to belief can occur if hoax information is highly correlated with hoax recipients, viral is discussed in the community, and is in accordance with personal views or logic. This acceptance can motivate the behavior of sharing information back due to the desire to be recognized as a trendsetter in disseminating the first information to the people around him. This is the main factor in the dissemination of Hoax information which needs to get recommendations for improving policies and strategies for eliminating Hoaxes in Indonesian society.